Amelanotic Melanoma Masquerading as a Granular Cell Lesion. (25th February 2013) - Pandiar, Deepak; Basheer, Shaini; Shameena, P. M.; Sudha, S.; Dhana, Lakshmi J.
Abstract : Amelanotic melanoma (AM) presents a diagnostic challenge due to its wide clinical presentations, lack of pigmentation, and varied histological appearances. Immunohistochemistry plays a crucial role in the diagnosis of these lesions. Amelanotic melanoma of oral mucosa is an uncommon lesion. We report a case of a 50-year-old male patient with a growth on the anterior mandibular gingiva of seven-month duration. In the present case, histologically, the tumour resembled a granular cell lesion, which has not been reported previously in AM. Diagnosis was possible by a sequential panel of immunohistochemical markers, of which finally vimentin, S100, HMB45, and Melan-A were positive. The tumor was surgically excised, and postsurgical radiotherapy was given.